Sequelae of the adult respiratory distress syndrome. - Hert, R. (1994)
Most survivors of ARDS have persistent mild reductions of TLCO even as long as a year after their episode. The lung volumes and flows return to normal in most instances, although a subset of patients will have persistent impairment. Both obstructive and restrictive deficits may be seen. This group may be predicted by the degree of acute lung injury assessed by the level of FIO2, PEEP, and gas exchange abnormality that exists in the first few days. In the first year after ARDS most physiological abnormalities will improve, but if deficits persist at one year further improvement is unlikely. Although many patients report dyspnoea following ARDS, the symptom does not correlate with abnormalities of pulmonary function. The possibility that conventional management may augment the degree of acute injury and worsen outcome must be considered. The effects of chronic hyperoxia in humans with acute lung injury or those of high levels of PEEP compared with low levels are not known. Exploring new ventilator management strategies while we await more specific treatment directed at the primary problem of acute lung inflammation will hopefully reduce acute mortality as well as acute and chronic morbidity.